Older Sibling or Younger Sibling? The Dynamics of Self-Confidence and Emotional Stability Among University Students in Wetland Communities - Muhammad Andri Setiawan; Nina Permata Sari; Hendro Yulius Suryo Putro; Andry Ananda Putra Tanggu Mara (Universitas PGRI Yogyakarta, 2026)
This study investigates the impact of birth order on self-confidence and emotional stability among university students residing in wetland communities. Using a quantitative survey design, 200 students, comprising 100 firstborns and 100 lastborns, from Lambung Mangkurat University were assessed using the Edwards Personal Preference Schedule (EPPS). Descriptive statistics, Mann-Whitney tests, and Structural Equation Modelling (SEM) were used to analyze the data. Results indicated that firstborn students exhibited significantly higher self-confidence (M = 3.57, SD = 1.26) and emotional stability (M = 3.43, SD = 1.26) than lastborns (p < .05). Family expectations and academic experiences emerged as key influences. SEM revealed that self-confidence strongly predicts emotional stability (β = 0.52, p < .001), with family background and educational experience having moderate effects. The findings underscore the psychological challenges faced by students in geographically isolated, resource-limited wetland environments. Tailored counseling interventions are recommended, particularly for lastborn students. Future research should investigate the intersection of cross-cultural and environmental factors. Keywords: self-confidence, emotional stability, birth order, wetland communities, Edwards Personal Preference Schedule (EPPS)